Kinerja Ruas Jalan Pada Zona Selamat Sekolah (ZoSS) di Jakarta Selatan - Lis Lesmini; Abdullah Ade Suryobuwono; Muhammad Iqbal Firdaus (Institut Transportasi dan Logistik Trisakti, 2020)
The School Safety Zone (ZoSS) is created to regulate traffic at certain times in areas close to schools to ensure the safety pedestrians in the area. However, this issue faces complex challenges, especially in schools located on strategic road corridors. The purpose of this study is to describe the traffic conditions of Ragunan Street, the factors that cause congestion on Ragunan Street at peak time and to describe the performance of the street located at the School Safety Zone (Zoss) of SMAN 28 Pasar Minggu, South Jakarta at peak times. The primary data source was obtained through traffic counting with a quantitative descriptive approach. The study population was passenger cars and motorbikes passing through Ragunan Street. The data analysis technique refers to the procedure for calculating urban roads according to the Indonesian Road Capacity Manual (MKJI) 1997. The results show that the performance of Ragunan Street is as follows; free flow speed of 57.52 km/hour, capacity 6,552 pcu/hour, the level of road service ranges from B to D. The degree of saturation is below 0.75 indicating the road capacity still meets the MKJI 1997 standard except for the direction of Kalibata-Pasar Minggu which scores 0.80 with a value of D. The speed in the ZoSS of SMAN 28 area is 57.52km/hour, significantly exceeding the maximum speed limit of 20-25 km/hour implying it is critical for pedestrians in the ZoSS area.